KEDUDUKAN ANAK PEREMPUAN DALAM SISTEM PEWARISAN MASYARAKAT ADAT BALI PASCA KEPUTUSAN MDP BALI TAHUN 2010 (STUDI KASUS DI KECAMATAN BANGLI, KABUPATEN BANGLI, PROVINSI BALI) - Jatiana Manik Wedanti I Gusti Ayu (VYAVAHARA DUTA, 2022)
Indigenous Balinese people who use a patrilineal system, after the issuance of the MDP Decree in 2010, slowly Balinese girls who were initially not entitled to any inheritance, even though they were also responsible for caring for their parents are now entitled to receive an inheritance from their families. The problem in this research is what is the position of women after the Bali MDP Decision 2010 in the inheritance of Balinese indigenous peoples and How is the existence of the Bali MDP Decree 2010 regarding inheritance in the Balinese Indigenous Peoples.The research method uses empirical juridical research methods. The conclusion obtained is that the girls have the right to receive inheritance in the form of inheritance from the Gunakaya property of their parents.The existence of the 2010 Bali MDP Decree is as a legal guide and as evidence of developments in Balinese customary law of inheritance.